Effect of sole and combined application of sulphatic micronutrients fertilisers on growth traits of wheat (Triticum aestivum L.) - Dhruvendra, S S; Prashun, S; Bhanu, S; Shivendra, S; Jay, S; Yogendra, P S; Ajay, P S (Plant Science Today, 2026)
Hidden hunger due to inadequate availability of micronutrients such as Zn, Fe and Cu often limits wheat productivity despite sufficient macronutrient supply. A field experiment was conducted during the rabi seasons of 2022–23 and 2023–24 at Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, to evaluate the effect of sulphate-based micronutrient fertilisation on the growth performance of wheat varieties. The study was laid out in a split-plot design with 2 varieties as main plots and 10 nutrient management treatments, including control, as subplots. Results revealed that variety DBW-222 exhibited superior growth performance over HD-2967 in terms of plant height, tiller density, dry matter production, crop growth rate and grain yield. Among nutrient management practices, the treatment, recommended dose of fertilisers (RDF) + soil application of (Zn + Fe+ Cu) through ZnSO4.7H2O at 20 kg ha-1, FeSO4.7H2O at 12 kg ha-1, CuSO4.5H2O at 2.0 kg ha-1 significantly enhanced plant height, tiller number, dry matter accumulation (DMA), crop growth rate (CGR) and grain yield compared to control and individual applications. This treatment also reduced days to heading and maturity, indicating improved crop vigour and growth efficiency. The period of 60–90 days after sowing (DAS) was identified as the most critical stage for rapid biomass accumulation. Overall, the study demonstrates that combined soil application of Zn, Fe and Cu substantially improves wheat growth and can be recommended as an effective strategy to address micronutrient deficiencies and enhance crop performance.